Self-organization of contact material CuCr structure in vacuum switch at electron beam action - Vasily Durakov; Sergey Gnyusov; Bair Dampilon; Svetlana Dekhonova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Electron beam cladding in vacuum was carried out according to the Archimedes spiral on copper billet of 80 mm diameter and 10 mm thickness. The authors have used a mixture of copper and chromium powders with chromium content fromf 20 to 50 wt. % for electron-beam cladding. Copper and chromium powder particle size was in the range from 90 to 125 microns. The comparison study of microstructures generated on the contact materials by vacuum arc surface melting and the microstructure of contact materials after electron beam cladding was carried out. The analysis of the microstructures was carried out using a scanning electron microscope Leo Evo 50 equipped with microanalysis by secondary and backscattered electrons. The authors identified the areas of preferential combustion of cathode spots on the surface of the sintered contact material. It is shown that copper evaporates preferentially during the surface melting of the contact material by vacuum arc and the surface layer is enriched in chromium. Surface melting zone has a non-uniform depth on the contact material. Surface melting areas of contact material alternate with areas having the original structure. In the surface melting areas a bimodal structure is formed. It consists of primary and secondary chromium precipitates of either micron or submicron size, respectively. CuCr clad coatings demonstrate a bimodal structure similar to the structure of the surface layer contacts of vacuum switches fused by short circuit currents. Thus, it is shown that the electron-beam cladding is self-organizing structure of the contact material similar to the surface layer structure of vacuum circuit breakers contacts formed at their operation.